The Effectiveness of China’s Twitter Diplomacy in Defending its Sovereignty in Taiwan 2022 - Rahmawati, Ulfa; Surwandono, Surwandono (Journal of Islamic World and Politics, 2025)
This article analyses the effectiveness of digital diplomacy as a tool of Chinese political communication to manage international public opinion on the status of Taiwan. Using the concept of digital diplomacy and content analysis, the author analyses data sourced from tweets from the Chinese Ministry of Foreign Affairs Twitter account and five Diplomat accounts using the NVivo application to see the narratives formed and the public's response to the narrative. This study found that the Chinese government and diplomats framed the "One China Principle" narrative with elements of history, ethnicity, and national identity. The narrative managed to gain attention and dominate global discourse and became the main frame of mind on the Taiwan issue, as shown by the high level of public engagement. However, China's digital diplomacy, which tends to be aggressive, one-way and non-interactive, has limited its effectiveness in shaping global public opinion because no intermediary can facilitate the acceptance of China's foreign policy, as evidenced by the analysis of the comment column that the public's tendency to support Taiwan is much higher than support for the dream of Chinese reunification.